H α morphologies of star clusters in 16 LEGUS galaxies: constraints on H II region evolution time-scales - Hannon, Stephen; Lee, Janice C; Whitmore, B C; Mobasher, B; Thilker, D; Chandar, R; Adamo, A; Wofford, A; Orozco-Duarte, R; Calzetti, D; Della Bruna, L; Kreckel, Kathryn; et al. (Monthly notices of the Royal Astronomical Society, 2022)
The analysis of star cluster ages in tandem with the morphology of their H ii regions can provide insight into the processes that clear a cluster’s natal gas, as well as the accuracy of cluster ages and dust reddening derived from Spectral Energy Distribution (SED) fitting. We classify 3757 star clusters in 16 nearby galaxies according to their H α morphology (concentrated, partially exposed, no emission), using Hubble Space Telescope (HST) imaging from the Legacy ExtraGalactic Ultraviolet Survey (LEGUS). We find: (1) The mean SED ages of clusters with concentrated (1-2 Myr) and partially exposed H ii region morphologies (2-3 Myr) indicate a relatively early onset of gas clearing and a short (1-2 Myr) clearing time-scale. (2) The reddening of clusters can be overestimated due to the presence of red supergiants, which is a result of stochastic sampling of the IMF in low mass clusters. (3) The age-reddening degeneracy impacts the results of the SED fitting - out of 1408 clusters with M* ≥ 5000 M⊙, we find that at least 46 (3 per cent) have SED ages which appear significantly underestimated or overestimated based on H α and their environment, while the total percentage of poor age estimates is expected to be several times larger. (4) Lastly, we examine the dependence of the morphological classifications on spatial resolution. At HST resolution, our conclusions are robust to the distance range spanned by the sample (3-10 Mpc). However, analysis of ground-based H α images shows that compact and partially exposed morphologies frequently cannot be distinguished from each other.
Gesehen am 22.04.2022